If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + u + -22 = 9(2) Reorder the terms: 15 + -22 + u = 9(2) Combine like terms: 15 + -22 = -7 -7 + u = 9(2) Multiply 9 * 2 -7 + u = 18 Solving -7 + u = 18 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + u = 18 + 7 Combine like terms: -7 + 7 = 0 0 + u = 18 + 7 u = 18 + 7 Combine like terms: 18 + 7 = 25 u = 25 Simplifying u = 25
| 6x+35=59 | | -4s--8=142 | | 9x-7-2x=56 | | -4t-15+8t=2t+19 | | 3x+7+2x-1=11 | | 7.8+6=23.16 | | 7.8+6=23.16 | | 126+22+4x=180 | | 6x-15=x+5(3+x) | | (x+3)(x+3)=8x | | 20-16y=-19-19y | | p+4b=120 | | 2x+x+(x+2)=30 | | -208=-21x+212 | | -11-22=33 | | 7(4x-5)-4(6x-5)=-91 | | -2j-20=8j | | 8z=122 | | 65+90+5x=180 | | -3-y-X=0 | | 2x-8=-8x-24 | | 2(4-9w)= | | 57+51+9x=180 | | 6(-2y-16)-2y=-12 | | 6p+b=144 | | -18s+10=-17s | | (X+18)=(x+10) | | 18x-12=17x-2 | | 0=-x+5y | | 3(2z)=-3 | | -690=10(-7x+22) | | 5x-9x+3=17 |